Quality of Life of Chronic Kidney Failure Patients Based on Hemodialysis Adherence at Lavalette Hospital - Wulansari, Ririh; Mawaddah, Nurul (PT Saintek Medika Nusantara, 2023)
The mortality rate in hemodialysis patients with low quality of life will increase compared to the average population. Quality of life is an essential indicator of the effectiveness of hemodialysis measures provided, so quality of life is also an essential goal in the treatment of end-stage renal failure disease. This study aimed to determine the relationship between compliance with hemodialysis and the quality of life of patients with chronic renal failure at Lavalette Hospital. This research method uses casual comparative research with a cross-sectional design. The sample was Chronic Kidney Failure patients who routinely performed hemodialysis, with as many as 98 respondents. The research instruments used were the End-Stage Renal Disease Adherence Questionnaire (ESRD-AQ) and quality of life instruments, which were also used on the KDQOL SFTM 1.3 scale. The data analysis method used chi-square correlation. The results showed that most of the respondents in the Hemodialysis Room of Lavalette Hospital Malang City were compliant with HD and had a good quality of life. The conclusion obtained from this study is that there is a relationship between HD compliance and quality of life in patients undergoing routine hemodialysis at Lavalette Hospital.